Model Kemandirian Masyarakat dalam Upaya Pemberdayaan Sosial melalui Program PKH di Kota Surabaya - Kokoh Prasetyo; Ertien Rining Nawangsari; Johan Vivaldi Alex Sander (Jurnal Penelitian Administrasi Publik, 2020)
Indonesia is a country that has quite a large population, one of which is the largest population in the city of Surabaya as a metropolis. With this large number of people, the poverty rate for families in the community is high, so the government provides a program to break the poverty chain, the Family Hope Program (PKH). The purpose of this study is to determine the implementation of social empowerment in the city of Surabaya through the family hope program that can make the community / beneficiary socially and economically independent life and measure the family hope program as a manifestation of community independence. This study used descriptive qualitative method. Data sources consist of primary data and secondary data. Primary data sources were obtained from observations and interviews. Data processing is done through the process of data reduction, data presentation, and conclusion checking or verification. The analysis used in this research is to use the basic principle model of community independence. The results of this study, show that social empowerment through the family of hope program by using a model of community independence is still not going well to create an economically and socially independent community. This can be seen from the data of the community / beneficiaries can live independently after receiving a family of hope program. Through the basic principle model of community independence from Sunyoto Usman (2003) which includes: creating climate, strengthening power, and protecting.Keywords: Human Development Index, Social Empowerment,Welfare